Consumption-Related Health Education Inequality in COVID-19: A Cross-Sectional Study in China - You, Jialu; Zhang, Jinhua; Li, Ze (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic influences various aspects of society, especially for people with low socioeconomic status. Health education has been proven to be a critical strategy in preventing a pandemic. However, socioeconomic characteristics may limit health education among low socioeconomic status groups. This study explores consumption-related health education inequality and the factors that contribute to this, which are variable across China during COVID-19. Methods The 2020 China COVID-19 Survey is a cross-sectional study in China, based on an anonymous online survey from 7,715 samples in 85 cities. It employed machine-learning methods to assess household consumption and other contributing variates associated with health education during the pandemic. Concentration Index (CI) and Horizontal Index (HI) were used to measure consumption-related inequalities in health education, respectively. Moreover, Wagstaff decomposition analysis was employed to identify other contributing variables to health education inequality. Results The result indicates that participants with more education, better income, and positive consumption preferences undertake higher health education during COVID-19. The CI and HI of consumption-health education inequality are 0.0321 (P < 0.001) and 0.0416 (p < 0.001), respectively, which indicates that health education is concentrated in wealthy groups. We adapted Lasso regression to solve issues and omit variables. In terms of other socioeconomic characteristics, Annual Income was also a major contributor to health education inequalities, accounting for 27.1% (P < 0.001). The empirical results also suggests that education, health status, identification residence, and medical health insurance contribute to health education inequality. Conclusions The difference in Household consumption, annual income, rural and urban disparity, and private healthcare insurance are critical drivers of health education inequality. The government should pay more attention to promoting health education, and healthcare subside policy among vulnerable people. Significantly to improve awareness of undertaking health education with lower education, rural residential, to enhance confidence in economic recovery and life after COVID-19.